Análisis de la gestión de la innovación en la industria, y su influencia en el sector metalmecánico del Distrito Metropolitano de Quito en el periodo 2009-2012 - Chicaiza Salgado, Edison Rubén (2014)
In the present investigation was conducted a study of Innovation Management in the metalworking sector of the Metropolitan District of Quito. Through an exploratory and bibliographical study the different concepts and theories of Innovation Management System are analyzed. Standards, measurement methods, models and indicators applicable management are determined. Ecuador's metalworking sector is described and then the engineering sector of the Metropolitan District is analyzed through field research management level is determined innovation in enterprises. The information obtained from this primary source is contrasted with the main indicators of the Activities of Science, Technology and Research (ACTI) 2009-2011 provided by the INEC.